Comparación in vitro de la microdureza y rugosidad superficial de resinas bulk fill después del desafío abrasivo con una pasta dental blanqueadora - Sojo Armas, Alessandra Julissa (2018)
Objetivo: Comparar la microdureza y rugosidad superficial in vitro en resinas Bulk Fill después de un desafío abrasivo con pasta blanqueadora. Materiales y métodos: Noventa especímenes de resinas Bulk Fill Filtek™ Bulk Fill (FB), Tetric® N-Ceram Bulk Fill (TNC), Opus Bulk Fill (OBF) fueron divididos en 6 grupos (n=15). El desafío abrasivo in vitro fue realizado con un cepillo eléctrico Oral B y una solución de 3,3 ml de pasta dental / agua destilada por 30 s. La microdureza y rugosidad superficial inicial y final fue evaluada a los 15 y 30 días. Los datos fueron analizados mediante estadística descriptiva e inferencial (U Mann Whitney) Resultados: La rugosidad superficial a los 15 días fue: FB (0.09± 0.03µm/0.17± 0.10 µm); TNC (0.16 ± 0.09 µm/0.20± 0.09µm) y OBF (0.13±0.09 µm/0.18±0.06 µm). A los 30 días fue: FB (0.10 ± 0.05 µm/0.12 ±0.06 µm); TNC (0.07±0.04 µm/0.16±0.07µm) y OBF (0.11±0.03 µm/0.22±0.12 µm). Hubo diferencias estadísticamente significativas para FB (p=0.003) y OBF (p=0.0008) a los 15 días. A los 30 días, las resinas que presentaron un aumento significativo en los valores de rugosidad fueron OBF (p<0.0001) y TNC (p=0.0011). En la microdureza superficial, a los 15 días fue: FB (63.49±15.10 kg/mm2 / 65.53±8.21kg/mm2); TNC (47.67±6.20 kg/mm2 / 46.67±6.43 kg/mm2) y OBF (47.33±4.57 kg/mm2 / 45.4±4.32 kg/mm2). Existe una disminución a los 15 días en la resina OBF (p=0.0001). Conclusiones: Existe un aumento en la rugosidad superficial de las resinas Bulk Fill a los 15 y 30 días. Hubo una disminución en la microdureza superficial para la resina Opus Bulk Fill a los 15 días. Aim: To compare in vitro the microhardness and surface roughness in Bulk Fill composites after an abrasive challenge with whitening toothpaste. Materials and methods: Ninety specimens of Bulk Fill Filtek ™ Bulk Fill (FB), Tetric® N-Ceram Bulk Fill (TNC), Opus Bulk Fill (OBF) composite were divided into 6 groups (n = 15).The in vitro abrasive challenge was performed with an Oral B electric toothbrush and a 3,3 ml solution of toothpaste / distilled water for 30 s. The microhardness and initial and final surface roughness was evaluated at 15 and 30 days. The data were analyzed by descriptive and inferential statistics ¬(Mann Whitney U Test). Results: The surface roughness at 15 days was: FB (0.09 ± 0.03μm / 0.17 ± 0.10 μm); TNC (0.16 ± 0.09 μm / 0.20 ± 0.09μm) and OBF (0.13 ± 0.09 μm / 0.18 ± 0.06 μm). At 30 days it was: FB (0.10 ± 0.05 μm / 0.12 ± 0.06 μm); TNC (0.07 ± 0.04 μm / 0.16 ± 0.07μm) and OBF (0.11 ± 0.03 μm / 0.22 ± 0.12 μm). There were statistically significant differences for FB (p = 0.003) and OBF (p = 0.0008) at 15 days. After 30 days, the Bulk Fill composite that showed significant increases in the roughness values were OBF (p <0.0001) and TNC (p = 0.0011). The surface microhardness at 15 days was: FB (63.49 ± 15.10 kg / mm2 / 65.53 ± 8.21kg / mm2); TNC (47.67 ± 6.20 kg / mm2 / 46.67 ± 6.43 kg / mm2) and OBF (47.33 ± 4.57 kg / mm2 / 45.4 ± 4.32 kg / mm2). There was a decrease after 15 days in the OBF composite (p = 0.0001). Conclusions: There was an increase in the surface roughness of Bulk Fill composite at 15 and 30 days. There was a decrease in surface microhardness for the Opus Bulk Fill composite after 15 days.